2016
DOI: 10.1002/cctc.201600846
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant‐Free Palladium Nanoparticles Encapsulated in ZIF‐8 Hollow Nanospheres for Size‐Selective Catalysis in Liquid‐Phase Solution

Abstract: Encapsulation of surfactant‐free Pd nanoparticles (NPs) in the metal–organic framework material ZIF‐8 hollow nanospheres was achieved. Pd@ZIF‐8 hollow nanospheres showed excellent size‐selective catalytic properties in the liquid‐phase hydrogenation of olefins. As a result of the uniform pore size of the ZIF‐8 shell (apertures of 3.4 Å), the catalyst showed high activity for the hydrogenation of 1‐hexene (1.9×8.2 Å) but very low activity for larger molecules such as cis‐cyclooctene (5.3×5.5 Å), trans‐stilbene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 38 publications
2
49
0
Order By: Relevance
“…Moreover, the size, composition and configuration of encapsulated metal clusters can also be controlled according to practical needs. With this method, core–shell structured metal clusters@MOF catalysts can be synthesized for various types of MOFs, such as ZIF‐8, UiO‐66 and MIL‐101. [6d]…”
Section: Metal Clusters Confined In Metal–organic Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the size, composition and configuration of encapsulated metal clusters can also be controlled according to practical needs. With this method, core–shell structured metal clusters@MOF catalysts can be synthesized for various types of MOFs, such as ZIF‐8, UiO‐66 and MIL‐101. [6d]…”
Section: Metal Clusters Confined In Metal–organic Frameworkmentioning
confidence: 99%
“…Lu et al reported an effective encapsulation method to incorporate MNPs with various sizes and compositions within ZIF‐8 crystals using PVP as a protective agent. [67c] Typically, the preformed MNP sols were first mixed with an aqueous solution of PVP, and the PVP‐stabilized MNPs were then transferred into the MOF synthetic solution. Because of the surface functionalization with PVP, the size and shape of the MNPs could be easily controlled in the polar solvents during MOF syntheses.…”
Section: Metal Clusters Confined In Metal–organic Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to supported NPs that are often found on the internal and external MOF surface, completely encapsulating the NPs can offer enhanced activity/selectivity in catalytic reactions ,. For these so‐called core–shell structures, the nanoparticles are typically made before the subsequent MOF synthesis . This smart architecture provides a convenient way to afford desired molecules, because the identity and orientation of the approaching substrate is strongly influenced by the MOF pore architecture.…”
Section: Metal Nanoparticle@mof Compositesmentioning
confidence: 99%